2022
DOI: 10.3390/f13010078
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Phenotypic Differentiation of Common Yew (Taxus baccata L.) Populations in the North-Western Part of the Balkan Peninsula

Abstract: Common or English yew (Taxus baccata L., Taxaceae) is a conifer species, native to Europe, northern Africa, Asia Minor and Caucasus. It is a dioecious, wind-pollinated and animal-dispersed tree, known for its high-quality wood and medicinal properties, albeit poisonous. The species is rare and has been legally protected at the European and national levels. In addition, its low population density and disjunct character of distribution have reinforced the need for its protection as regeneration is mostly lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Similar results (84% and 16%) were obtained in the study of [29] and in [64], where 11% of variation was found among and 89% within populations. Moreover, similar results were obtained in the morphometric studies of [66], where sexual dimorphism was studied in Serbia, and in a study of seven populations from the northwestern part of the Balkan Peninsula where variability was also found and was correlated with geographic structure [67].…”
Section: Discussionsupporting
confidence: 79%
“…Similar results (84% and 16%) were obtained in the study of [29] and in [64], where 11% of variation was found among and 89% within populations. Moreover, similar results were obtained in the morphometric studies of [66], where sexual dimorphism was studied in Serbia, and in a study of seven populations from the northwestern part of the Balkan Peninsula where variability was also found and was correlated with geographic structure [67].…”
Section: Discussionsupporting
confidence: 79%